2012
DOI: 10.1186/1472-6890-12-11
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of matrix metalloproteinase expression in ameloblastoma

Abstract: BackgroundAn ameloblastoma is a benign odontogenic neoplasm with aggressive behaviour and high recurrence rates. The increased expression of matrix metalloproteinases (MMPs) has been reported in ameloblastomas. In the present study, we hypothesised that epigenetic alterations may regulate MMP expression in ameloblastomas.MethodsWe investigated the methylation status of the genes MMP-2 and MMP-9 in addition to mRNA transcription and protein expression in ameloblastomas. Methylation analysis was performed by bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 31 publications
(37 reference statements)
1
24
0
1
Order By: Relevance
“…Estimation of DNA methylation revealed hypomethylation at the promoter regions of MMP2 and MMP9 in placental villi, suggesting a similar role of DNA hypomethylation in activating expression of these invasion-promoting genes in placental tissue, as observed in the cancerous tissue (Shukeir et al 2006, Farias et al 2012. Emerging evidences suggest a significant role of chromatin-remodeling complexes in regulating expression of MMPs (Yan et al 2003, Chang et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…Estimation of DNA methylation revealed hypomethylation at the promoter regions of MMP2 and MMP9 in placental villi, suggesting a similar role of DNA hypomethylation in activating expression of these invasion-promoting genes in placental tissue, as observed in the cancerous tissue (Shukeir et al 2006, Farias et al 2012. Emerging evidences suggest a significant role of chromatin-remodeling complexes in regulating expression of MMPs (Yan et al 2003, Chang et al 2006.…”
Section: Discussionmentioning
confidence: 99%
“…MSP analysis for human MMP-2 was performed as described previously (Chernov et al. 2009; Farias et al 2012) (see Fig. S1A).…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, no difference was observed in the expression of MMP-9 between ameloblastoma and AOT. This result does not reflect the distinct patterns of aggressiveness seen in such tumors, such as suggested by the findings of Farias et al [17] and Henriques et al [18].…”
Section: Discussionmentioning
confidence: 42%